The Role of Hypoxia in Endometrial Cancer - Salinas-Vera, Yarely M.; Gallardo-Rincón, Dolores; Ruíz-García, Erika; Silva-Cázares, Macrina B.; de la Peña-Cruz, Carmen S.; López-Camarillo, César (Current Pharmaceutical Biotechnology, 2022)
Endometrial cancer represents the most frequent neoplasia from the corpus uteri and comprises the 14th leading cause of death in women worldwide. Risk factors that contribute to the disease include early menarche, late menopause, nulliparity, and menopausal hormone use, as well as hypertension and obesity comorbidities. The clinical effectiveness of chemotherapy is variable, suggesting that novel molecular targeted therapies against specific cellular processes associated with the maintenance of cancer cell survival and therapy resistance ameliorate the rates of success in endometrial cancer treatment. In the course of tumor growth, cancer cells must adapt to decreased oxygen availability in the microenvironment by upregulation of hypoxia-inducible factors, which orchestrate the activation of a transcriptional program leading to cell survival. During this adaptative process, the hypoxic cancer cells may acquire invasive and metastatic properties as well as increased cell proliferation and resistance to chemotherapy, enhanced angiogenesis, vasculogenic mimicry, and maintenance of cancer cell stemness, which contribute to more aggressive cancer phenotypes. Several studies have shown that hypoxia-inducible factor 1 alpha (HIF-1α) protein is aberrantly overexpressed in many solid tumors of the breast, prostate, ovarian, bladder, colon, brain, and pancreas. Thus, it has been considered an important therapeutic target. Here, we reviewed the current knowledge of the relevant roles of cellular hypoxia mechanisms and HIF-1α functions in diverse processes associated with endometrial cancer progression. In addition, we also summarize the role of microRNAs in the posttranscriptional regulation of protein-encoding genes involved in the hypoxia response in endometrial cancer. Finally, we pointed out the need for urgent targeted therapies to impair the cellular processes activated by hypoxia in the tumor microenvironment.
Keywords: therapy